Effective Immune Protection of Mice from Murine Cytomegalovirus Infection by Oral Salmonella-Based Vaccine Expressing Viral M78 Antigen - Yujun Liu; Hao Gong; Jiaming Zhu; Fenyong Liu (Vaccines)
Background: Human cytomegalovirus (CMV) is the most common cause of viral congenital infections worldwide. The development of effective vaccines against human CMV infection and disease is a high priority. Attenuated Salmonella are attractive oral vaccine vectors against human diseases because they can be administrated orally. Methods: In this study, an attenuated Salmonella strain was generated as an oral vaccine vector for the delivery and expression of the M78 protein of murine cytomegalovirus (MCMV). Using the MCMV infection of mice as the CMV infection model, we characterized the immune responses and protection induced by the constructed Salmonella-based vaccine. Results: The generated Salmonella-based vaccine, v-M78, which contained an M78 expression plasmid construct, carried out gene transfer efficiently for M78 expression and showed little pathogenicity and virulence in mice. In orally vaccinated mice, v-M78 induced anti-MCMV serum IgG and mucosal IgA responses and also elicited anti-MCMV T cell responses. Furthermore, mice immunized with v-M78 were protected from intraperitoneal and intranasal challenges with MCMV. The v-M78 vaccination reduced the titers of the challenged viruses in spleens, livers, lungs, and salivary glands. Conclusions: These results provide the first direct evidence that a Salmonella-based vaccine expressing M78 elicits strong humoral and cellular immune responses and induces immune protection against MCMV infection. Furthermore, our study demonstrates the potential of using Salmonella-based oral vaccines against CMV infection.